Pelatihan English For Specific Purpose Bagi Siswa SMK Negeri 1 Jember - Vigo Dewangga; Enik Rukiati; Nodistya Septian Indrastana; Renata Kenanga Rinda; Yuslaili Ningsih (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2024)
This community service focuses on ESP related to Visual Communication Design. The community service team will provide specialized English instruction related to Visual Communication Design, aligning with the subjects studied by students at SMK Negeri 1 Jember. This community service aims to impart knowledge to SMKN 1 Jember students regarding ESP in Visual Communication Design and to provide training so that they can effectively apply visual language through images, wordplay, and informative and communicative message processing. The method used, such as preliminary studies, preparation and implementation in training, as well as internal and external evaluation This community service involves students from SMKN 1 Jember, specifically those in the 10th grade of the Visual Communication Design department. The results of the community service demonstrate that 33 students (91.6%) of SMKN 1 Jember are proficient in developing and effectively applying visual language for informative and communicative purposes. While 3 students (8.3%) still have not mastered it.